The Influence of Social Media Marketing on Brand Loyalty: Evidence from Malaysian Youth in the Ride-Hailing Sector - Lay Hong Tan; Gai Sin Liem; Siti Nurul Alia Binti Salehuddin; Siti Nurul Izzati Binti Amirrullah; Kai Xuan Sok; Stephanie Jing E Yong; Su Jinghan; Anees Jane Ali; Daisy Mui Hung Kee (AIBPM Publisher, 2025)
Grab, founded in 2012, is a leading multi-service platform in Southeast Asia that actively uses social media to build relationships and foster brand loyalty. This study investigates the influence of social media marketing on brand loyalty among Malaysian youth aged 15–40, emphasizing the mediating role of customer satisfaction. A quantitative approach was employed through an online survey of 119 respondents, and data were analyzed using regression analysis. Results show that brand trust (? = 0.376, p 0.001), perceived social media interaction quality (? = 0.192, p 0.05), and loyalty program engagement (? = 0.245, p 0.01) significantly influence customer satisfaction (R² = 0.608). Meanwhile, customer satisfaction (? = 0.717, p 0.001) and loyalty program engagement (? = 0.315, p 0.001) have significant positive effects on brand loyalty (R² = 0.635), whereas brand trust and social media interaction quality show no direct influence. These results confirm that customer satisfaction mediates the effects of trust, interaction quality, and loyalty program engagement on loyalty. The study concludes that loyalty programs and customer satisfaction are key drivers of sustained loyalty, highlighting the need for brands like Grab to strengthen personalized engagement and satisfaction-based strategies for young digital consumers.